Toxic liver disease after intentional paracetamol abuse for a suicide attempt in a 15-year-old girl - Mania, Anna; Jowik, Katarzyna; Mazur, Katarzyna; Kemnitz, Paweł; Służewski, Wojciech; Figlerowicz, Magdalena (Pediatria Polska - Polish Journal of Paediatrics, 2018)
We present a case of a 15-year-old girl who was admitted to hospital due to vomiting, diarrhoea, jaundice, and fever, which were observed for about a week. Liver dysfunction was found in laboratory tests, and the diagnostic process suggested autoimmune hepatitis. Anamnesis and new information from the patient’s family members led to the diagnosis of toxic liver disease after intentional paracetamol abuse for a suicide attempt. There were some essential risk factors: teenage, female sex, serious family troubles. The use of paracetamol for the purpose of suicide is a frequent phenomenon. Because of the increasing number of suicides in teenagers in Poland, it seems to be important to remind to paediatricians about their reasons and risk groups, as well as about clinical and laboratory symptoms of paracetamol poisoning.